Study on the ecological risk of the sediment from the Hangzhou section of the Grand Canal, China, with potential ecological risk index - HE Yun-feng; ZHU Guang-wei; CHEN Ying-xu; TIAN Guang-ming; CHEN Hua-lin (浙江大学学报. 农业与生命科学版)
The ecological risk of the sediment of the Hangzhou section of the Grand Canal was studied with potential ecological risk index. The results showed that, potential ecological risk of heavy metals in the sediment decreased as followed: Cd > Hg > Cu > Pb > As > Zn > As. Cd is the most hazardous elements with the mean ecological risk factor of 195. Although Zn has the highest geological accumulation factor, its ecological risk was low. Ecological risk of heavy metals of the sediment belong to Cd-type in the section from Sanbao shipping lock to Genshan bridge; it belong to Cd-Hg combined type in the Genshan to Daguan bridge section. In Daguan to Yi bridge section and Yi to Tangxi bridge section, the ecological risk of the sediment belong to multi-element type and Cd-Hg combined type, respectively. This study suggested that potential ecological risk index is a practical method for the ecological risk evaluation of the heavy metal in sediment of urban canal.